2002
DOI: 10.1046/j.1537-2995.2002.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of HCV core antigen and HCV RNA detection in the early infection phase

Abstract: A majority of HCV RNA-positive samples were also cAg-positive during the PWP. The current cAg detection corresponds to 100,000 IU per mL of HCV RNA. Since low-titer samples would be identified only by single-donation NAT, which is often affordable only in developed countries, the cAg ELISA could offer a practical alternative for some countries. The doubling time for HCV RNA at the onset of viremia corresponds to a calculated mean delay of cAg detection during the virus burst phase of 2 or 5 days, when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
97
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 27 publications
12
97
1
2
Order By: Relevance
“…The detection and quantification of HCV core antigen in the serum or plasma of infected patients by using different assay formats were previously shown to narrow the preseroconversion (window) phase of acute HCV infections (26,30) and to be a useful marker of viral replication (4,5,11,13,23,34,42,47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detection and quantification of HCV core antigen in the serum or plasma of infected patients by using different assay formats were previously shown to narrow the preseroconversion (window) phase of acute HCV infections (26,30) and to be a useful marker of viral replication (4,5,11,13,23,34,42,47).…”
Section: Discussionmentioning
confidence: 99%
“…Translation of the results obtained with the Architect HCV Ag assay with the samples from the seroconversion panels into the biology of acute HCV infections would mean that the test is probably able to detect HCV in all specimens from patients with infections in the plateau phase. It is also conceivable that the Architect assay may recognize HCV in a considerable portion of samples from patients in the ramp-up phase but will definitely miss HCV in specimens taken from patients in the pre-ramp-up phase of acute HCV infection (12,30). Additional testing of blood donors for the presence of HCV core antigen will, hence, lead to improved blood safety compared to that achieved by the use of third-generation anti-HCV tests alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate diagnosis of HCV infection is important due to the morbidity associated with the virus, and determining the level of viral replication is important in predicting and monitoring the effect of antiviral treatment. Although quantifying viral RNA represents the standard method for identifying active infection (5,8,13), several sensitive immunoassays that detect the viral core antigen (Ag) have now been developed as an alternative to HCV RNA testing (3,4,6,9,10,12,16). The amino acid sequence of the core Ag is largely conserved among different viral isolates (14); however, genetic variability of the virus constitutes one of the major challenges to using core Ag assays for diagnosis.…”
mentioning
confidence: 99%
“…In addition, some authors emphasized the clinical advantage of HCV core Ag quantification as a direct marker of viral replication in the chronic phase of infection (4) and as a relevant marker for predicting and monitoring the response to therapy (7,29,31). Indeed, the HCV core Ag assays have sensitivities close to that of NAT, with mean detection differences of 1 to 2 days in the window period with the specific assay developed for blood screening (11,32,35,45) and 0.29 day with the immunoassay capable of detecting and quantifying HCV core Ag (23). A recent study reported that a prototype assay based on the simultaneous detection of HCV core Ag and anti-HCV Ab significantly closed the time gap between HCV RNA detection and the first appearance of detectable anti-HCV Ab (42).…”
mentioning
confidence: 99%